2019
DOI: 10.1177/2050313x19857392
|View full text |Cite
|
Sign up to set email alerts
|

Chronic annular pustular psoriasis resembling subcorneal pustular dermatosis: A case report

Abstract: Generalized pustular psoriasis and subcorneal pustular dermatosis are generalized pustular dermatoses that are characterized by the subcorneal accumulation of neutrophils. Careful examination is important in distinguishing these diseases for appropriate management. Patients with acute generalized pustular psoriasis are systemically unwell with discrete pustules as opposed to the chronicity and associated hypopyon lesions in subcorneal pustular dermatosis. Generalized pustular psoriasis lesions demonstrate psor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 12 publications
(17 reference statements)
0
14
0
Order By: Relevance
“…However, the hallmark features of GPP include classic psoriasiform changes seen in the epidermis, such as parakeratosis and elongation of rete ridges. 7 In GPP, neutrophils that migrate from dilated vessels in the papillary dermis into epidermis aggregate beneath the stratum corneum to form the 'spongiform pustules of Kogoj' . 8 The histopathological result in our case suited the characteristic of GPP.…”
Section: Discussionmentioning
confidence: 99%
“…However, the hallmark features of GPP include classic psoriasiform changes seen in the epidermis, such as parakeratosis and elongation of rete ridges. 7 In GPP, neutrophils that migrate from dilated vessels in the papillary dermis into epidermis aggregate beneath the stratum corneum to form the 'spongiform pustules of Kogoj' . 8 The histopathological result in our case suited the characteristic of GPP.…”
Section: Discussionmentioning
confidence: 99%
“…GPP, on the other hand, reveals the classic psoriasiform changes, parakeratosis, elongation of rete ridges, spongiform pustules of Kogoj, and acantholysis. 4 The treatment of choice in children is dapsone, similar to what is indicated for adults. However, cases of hematologic toxicity from the drug have been reported in children, mainly hemolytic anemia and methemoglobinemia.…”
Section: Case Reportmentioning
confidence: 99%
“…Histopathologically, the most commonly described feature of both SPD and generalized pustular psoriasis (GPP) is neutrophil accumulation within the epidermis. In addition, annular GPP is often similar to SPD in form 3 . Therefore, it is suggested that some cases of SPD may represent a variant of GPP.…”
Section: Figurementioning
confidence: 99%